Importance of the information systems in public health programs: diabetic patients databases - Naeko Uema, Sonia Andrea; Olivera, María Eugenia (Ars Pharmaceutica (Internet), 2013)
Aims: To describe the characteristics of diabetic patients’ population attended in the public health sector of Alta Gracia city. To analyze the use of amount of monthly dispensations as indicator of adherence to treatment, by comparing the results between settings. To assess the coordination of public facilities for patients attention. Materials and methods: Design: observational descriptive-analytical study. Settings: Hospital Arturo Umberto Illia (HAUI) and Dirección de Salud Pública (DSP). Alta Gracia (province of Córdoba, Argentina). Subjects: diabetic patients belonging to health programs at public facilities. Main measures: demographic and epidemiological variables, amount of monthly dispensations, percentage of global adherence and coordination of settings. Results: From diabetic patients’ total (n=540): 52% were attended at HAUI, 39% at DSP, and 9% at both settings; 55% were female, and the average age was about 56 years old; 81% were type 2 Diabetes Mellitus (DM), 1% type 2 insulin-requiring DM, and 17% type 1 DM; the general mean of amount of monthly dispensations by patient was 4.9 in 12 months. Lack of trained personnel for information managing in both facilities was observed. Conclusions: The databases allowed knowing some demographic characteristics of diabetic population attended in the public sector of Alta Gracia. The dispensing frequency during 12 months was able to be used as an adherence to treatment indicator. The scarce coordination between care levels and jurisdictions (provincial and municipal) were confirmed. For decision making it is necessary to generate and maintain information systems.